New Method to Determine the Effect of Surface PEGylation on Cellular Uptake Efficiency of Mesoporous Silica Nanoparticles with AIEgens. Issue 13 (15th May 2018) - Yuan, Qian; Wang, Ke; Zhang, Xiaoyong; Zhang, Xiqi; Wei, Yen
Abstract: Mesoporous silica nanoparticles (MSNs) with various surface modifications are extensively investigated for drug/gene delivery. However, it is still not quite facile to determine the accurate effects of surface modification on their cellular uptake by now. In this report, a semiquantitative method is described to evaluate the cellular internalization efficiency of PEGylated MSNs with the help of aggregation induced emission (AIE)‐active luminogen (AIEgen) and ImageJ. First, AIEgen is facilely incorporated into nanoparticles to obtain fluorescent MSNs and PEGylated MSNs with the same emission density and similar particle sizes. Then their cellular uptake efficiency in L929 cells is determined by analyzing their cellular imaging results with ImageJ, which demonstrates that more than 25% PEGylated MSNs can get into cells than MSNs after 8 h. This approach can not only be utilized for evaluating the cellular uptake efficiency of other nanoparticles but can also provide useful information for their further biomedical applications. Abstract : A facile strategy is established to determine the effect of surface PEGylation on cellular uptake of the mesoporous silica nanoparticles (MSNs) with the help of superior aggregation induced emission (AIE)‐active luminogen (AIEgen) and a versatile software ImageJ. The results demonstrate that more than 25% PEGylated MSNs can get into L929 cells in 8 h than MSNs.